Development of a technical service enterprise management principles - M. Yu. Kolovertnova; A. P. Tyapukhin (Вестник университета)
In order to achieve operational and strategic goals, a technical service enterprise, with the help of management principles, affects management facilities, resources, equipment, machinery, technologies, personnel, customers and partners. Despite the relative stability of the content and structure of the principles of enterprise management, they can be implemented in various ways and are subject to changes depending on the state and trends of environmental development. The article is devoted to clarifying and supplementing the number and interrelationships of management principles of technical service enterprises. It uses methods of analysis and synthesis, induction and deduction, as well as classification, and the tools are binary matrices that provide for the joint use of qualitative features of the studied management principles and their dichotomies. The results obtained make it possible to reduce costs, time, as well as lost profits in the field of technical service due to a clear structuring of management principles by levels of enterprise management and positions provided for by its staffing schedule.